On the Origins of the Fleming-Mundell Model - Boughton, James (IMF Working Papers; Working Paper, 2002)
Forty years ago, Marcus Fleming and Robert Mundell developed independent models of macroeconomic policy in open economies. Why do we link the two, and why do we call the result the Mundell-Fleming, rather than Fleming-Mundell model?.